RESILIENSI DIRI DAN STRES KERJA PADA GURU SEKOLAH DASAR - ZARINA AKBAR; RIZKY PRATASIWI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
This Research aims to review the relationship between resiliensi and job stress on primary school teachers.This research using quantitative methods.Samples to this study were 100 (n = 100) using purposive sampling technique.The data using a questionnaire resilience quotient test and teacher stress inventory (TSI). The analysis used using spss 23.0 version. Based on the research, we got the result of notation statistics r = -0.41; p = 0.000 < 0.05 (significant). The result of this research indicated there are significant negative relationship between resiliensi themselves to stress work in primary school teachers. Much value p produced is -0.41 on significance 0.05 standard.